Using direct linear transformation (DLT) method for aerial photogrammetry applications - El-Ashmawy, Khalid L. A. (Geodesy and Cartography, 2018)
DLT has gained a wide popularity in close range photogrammetry, computer vision, robotics, and biomechanics. The wide popularity of the DLT is due to the linear formulation of the relationship between image and object space coordinates. This paper aims to develop a simple mathematical model in the form of self calibration direct linear transformation for aerial photogrammetry applications. Software based on the derived mathematical model has been developed and tested using mathematical photogrammetric data. The effects of block size, number and location of control points, and random and lens distortion errors on self calibration block adjustments using the derived mathematical model and collinearity equations have been studied. It was found that the accuracy of the results of self calibration block adjustment using the derived mathematical model is, to some extent, comparable to the results with collinearity model. The developed mathematical model widens the application areas of DLT method to include aerial photogrammetry applications especially when the camera interior and exterior orientations are unknown.